Trust and distrust as distinct concepts. A framework for the public sector - Marzec, Małgorzata; Świrska, Anna (Management and Administration Journal, 2019)
In the global rankings of generalized trust, Poland occupies a low position. Polish people are rather distrustful. Analyses of trust endeavour to isolate (distinguish) distrust. Distrust is more and more often defined as a separate definition, not only as the opposite to trust. Analysis of distrust seems indispensable, in particular with reference to the public sector. Public sector organizations point out at building trust. The article is an attempt to systematize the concept of distrust through analysis of trust and separation of basic differences in both concepts (trust and distrust) was made. A great significance of distrust towards entities (organizations) of the public sector may be observed. The objective of the article and research was to prepare a theoretical basis for the studies on distrust in the Polish public sector. The paper includes theoretical frameworks, which may be used for a detailed research on the role and significance of distrust in the public sector. The paper is based on the literature review and generally available data.